Number of repetitions used in strength training for weight loss: a systematic review - Silva Filho, José Nunes da (2014)
For World Health Organization in 2013, overweight and obesity are the main cause of many systemicdiseases, representing the fifth overall risk of death by killing some 2.8 million adults per year. And strength training has been proposed as an aid in the prevention and treatment of obesity. Aim: the study was to evaluate evidence on one of the training variables (number of repetitions) used in studies on the effects of strength training focused on weight loss. Methods: The study is a systematic review, described following the PRISMA recommendations. The search data began with the selection of key termsand their synonyms, following the health descriptors in Desc (http://decs.bvs.br) and Mesh (http://www.ncbi.nlm.nih.gov/mesh/). After that, he began a filter in the main bases of national and international data: Scielo; PubMed, and Google Scholar search site aiming to recover other possible studies of journals not indexed in the databases mentioned. Results: after established eligibility criteria, 17 clinical trials showed that mean and standard deviation of (9.59 ± 2.47) to (12.47 ± 2.83) repetitions. Conclusion: we conclude that the number of repetitions in strength training aimed at weight loss should be between (9 to 12 ± 2).